α-Synuclein is required for sperm exocytosis at a post-fusion stage - Micaela Vanina Buzzatto; Micaela Vanina Buzzatto; María Victoria Berberián; María Victoria Berberián; María Victoria Berberián; Ary Lautaro Di Bartolo; Diego Masone; Diego Masone; Claudia Nora Tomes; Claudia Nora Tomes (Frontiers in Cell and Developmental Biology, 2023)
The sperm acrosome is a large dense-core granule whose contents are secreted by regulated exocytosis at fertilization through the opening of numerous fusion pores between the acrosomal and plasma membranes. In other cells, the nascent pore generated when the membrane surrounding a secretory vesicle fuses with the plasma membrane may have different fates. In sperm, pore dilation leads to the vesiculation and release of these membranes, together with the granule contents. α-Synuclein is a small cytosolic protein claimed to exhibit different roles in exocytic pathways in neurons and neuroendocrine cells. Here, we scrutinized its function in human sperm. Western blot revealed the presence of α-synuclein and indirect immunofluorescence its localization to the acrosomal domain of human sperm. Despite its small size, the protein was retained following permeabilization of the plasma membrane with streptolysin O. α-Synuclein was required for acrosomal release, as demonstrated by the inability of an inducer to elicit exocytosis when permeabilized human sperm were loaded with inhibitory antibodies to human α-synuclein. The antibodies halted calcium-induced secretion when introduced after the acrosome docked to the cell membrane. Two functional assays, fluorescence and transmission electron microscopies revealed that the stabilization of open fusion pores was responsible for the secretion blockage. Interestingly, synaptobrevin was insensitive to neurotoxin cleavage at this point, an indication of its engagement in cis SNARE complexes. The very existence of such complexes during AE reflects a new paradigm. Recombinant α-synuclein rescued the inhibitory effects of the anti-α-synuclein antibodies and of a chimeric Rab3A-22A protein that also inhibits AE after fusion pore opening. We applied restrained molecular dynamics simulations to compare the energy cost of expanding a nascent fusion pore between two model membranes and found it higher in the absence than in the presence of α-synuclein. Hence, our results suggest that α-synuclein is essential for expanding fusion pores.